WIDEN: A tool for medical image management in multicenter clinical trials. (June 2014) - Chauvie, Stéphane; Biggi, Alberto; Stancu, Alexandru; Cerello, Piergiorgio; Cavallo, Anna; Fallanca, Federico; Ficola, Umberto; Gregianin, Michele; Guerra, Ugo Paolo; Chiaravalloti, Agostino; Schillaci, Orazio; Gallamini, Andrea
Background: It has been proposed that in clinical trials in which the therapeutic strategy is driven by functional imaging, central review of the images should be done in real time. Purpose: We report our experience with a new tool for image exchange and review, called Web-Based Imaging Diagnosis by Expert Network (WIDEN), which we implemented for the HD0607 prospective multicenter Italian clinical trial in which Hodgkin lymphoma treatment was adapted based on results of an interim positron emission tomography (PET) scan performed after the first two cycles of chemotherapy. Methods: We used WIDEN for general management of the clinical trial, site imaging qualification, image exchange, workflow control, blinded independent central review, inter-observer variability assessment, consensus creation, audit, and statistical analysis. Results: As of February 2013, the interim PET was available for 512 patients; upon central review, 103 of the scans were judged to be positive and 409 to be negative. The median scan uploading and downloading times were 1 min, 25 s and 1 min, 55 s, respectively; the average and median times for diagnosis exchange were 47 h, 53 min and 37 h, 43 min, respectively. The binary concordance between pairs of reviewers (Cohen's kappa) ranged from 0.72 to 0.85. The 5-point scale concordance among all reviewers (Krippendorf's alpha) was 0.77. Conclusions: WIDEN proved to be an effective tool for medical imaging exchange and online review. Data security, simplicity, feasibility, and prompt scan review were demonstrated. Central reviews were completed promptly.